Variability, Correlation and Path Analysis for Several Quantitative Traits Derived Multi-Parent Advanced Generation Inter-Cross (Magic) F2 Population of Rice (Oryza sativa L.) - Thúy, Lưu Thị; Vu, Thi-Nhuong; Pham, Van-Tinh; Nguyen, Anh-Dung; Nguyen, Trong-Khanh (International Journal of Scientific Research and Management (IJSRM), 2022)
Eight quantitative traits of an F2 MAGIC population in rice were subjected to analyze variability, correlation and path analysis. The results of third and fourth degree statistics (skewness and kurtosis) showed that Individual dried straw weight, 1000-seed weight, Individual grain yield, and Number of effective tillers are associated with complementary gene interaction, requiring intense selection, while Plant height, Panicle length, Spikelet fertility percentage, and Harvest index are associated with duplicate (additive x additive) gene interactions, are suitable for mild selection. Leptokurtic distribution of Plant height, Number of effective tillers per plant, Pancile length and Spikelet fertility percentage revealed that the large number of genes in governing the traits. Platykurtic distribution of Individual dried straw weight, 1000-seed weight, Individual grain yield and Harvest index indicated fewer genes controlling the traits. However, when it comes to H2 and GAM, high values were seen in Number of effective tillers per plant, Individual dried straw weight, Individual grain yield, the traits could be explained by additive gene action and achieved through mass selection. High heritability and lower GAM of Plant height, Panicle length, 1000-seed weight and Harvest index indicated by non-additive genes with limiting the chances of direct selection. For the Pearson correlation, 1000-seed weight showed no correlation with other traits. Individual grain yield highly correlated with Number of effective tillers per plant (0.864**) and Individual dried straw weight (0.828**). The highest total effects on Individual grain yield were Number of effective tillers per plant (2.7437) and Individual dried straw weight (1.0865). Individual dried straw weight had highest direct effect on Individual grain yield at 1.0734, while most of the traits showed high indirect effect on Individual grain yield through Individual dried straw weight.